The Transformation of Betangas in Contemporary Malay Society: From Communal Rituals to Modern Care - Fitriah, Fitriah; Cholidi, Cholidi; Syawaludin, Mohammad (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
This study examines betangas, a traditional Malay steam-bathing practice, as a dynamic cultural ritual undergoing transformation in contemporary society. Previous studies have largely approached betangas from descriptive ethnobotanical or functional perspectives, emphasizing plant knowledge, ritual stages, or symbolic meanings, while paying limited attention to its ongoing transformation within changing social structures. Addressing this gap, the present research analyzes betangas as a cultural practice that is continuously reconfigured in response to modernity, shifting bodily regimes, and changing knowledge authorities. Drawing on an ethnographic approach with historical and cultural perspectives, this study integrates literature analysis with field-based insights from Malay communities in South Sumatra to capture both continuity and change in practice. The findings reveal three interrelated patterns of transformation: the expansion of betangas from a pre-marital communal ritual into therapeutic, relaxation, and cosmetic practices; the shift from collective, family-based rituals to more individualized and service-oriented forms; and the reproduction of local ethnobotanical knowledge into scientific, educational, and commercial formats. These transformations reflect broader processes of rationalization, individualization, and commodification of traditional knowledge, while simultaneously generating new forms of legitimacy for betangas in contemporary health and lifestyle contexts. Rather than signaling cultural decline, the transformation of betangas demonstrates a process of reinterpretation and adaptation, where ritual meanings, bodily practices, and local knowledge are renegotiated within modern social, economic, and epistemic frameworks. This study contributes to debates on ritual change, the sociology of the body, and postcolonial discussions on the commodification of indigenous knowledge, highlighting how traditional body care practices persist through transformation rather than disappearance. Keywords: Abstrak. Penelitian ini mengkaji betangas, sebuah praktik mandi uap tradisional Melayu, sebagai ritual budaya yang dinamis dan terus mengalami transformasi dalam masyarakat kontemporer. Kajian-kajian sebelumnya cenderung menempatkan betangas dalam kerangka deskriptif etnobotani atau fungsional, dengan menekankan pengetahuan tumbuhan, tahapan ritual, atau makna simbolik, namun masih terbatas dalam membahas proses transformasi praktik ini dalam konteks perubahan struktur sosial. Menjawab celah tersebut, penelitian ini menganalisis betangas sebagai praktik budaya yang senantiasa direkonfigurasi seiring dengan modernitas, perubahan rezim tubuh, dan pergeseran otoritas pengetahuan. Dengan menggunakan pendekatan etnografis yang diperkaya perspektif historis dan kultural, penelitian ini memadukan kajian literatur dengan temuan lapangan pada komunitas Melayu di Sumatera Selatan untuk menangkap dinamika kesinambungan dan perubahan praktik betangas. Hasil penelitian menunjukkan tiga pola transformasi yang saling terkait, yaitu: perluasan fungsi betangas dari ritual komunal pra-nikah menjadi praktik terapeutik, relaksasi, dan kosmetik; pergeseran dari ritual kolektif berbasis keluarga menuju bentuk praktik yang lebih individual dan berbasis layanan; serta reproduksi pengetahuan etnobotani lokal ke dalam format ilmiah, edukatif, dan komersial. Transformasi ini mencerminkan proses rasionalisasi, individualisasi, dan komodifikasi pengetahuan tradisional, sekaligus membentuk sumber legitimasi baru bagi betangas dalam konteks kesehatan dan gaya hidup kontemporer. Alih-alih menunjukkan kemunduran budaya, transformasi betangas memperlihatkan proses reinterpretasi dan adaptasi, di mana makna ritual, praktik tubuh, dan pengetahuan lokal dinegosiasikan ulang dalam kerangka sosial, ekonomi, dan epistemik modern. Penelitian ini berkontribusi pada perdebatan tentang perubahan ritual, sosiologi tubuh, serta kajian poskolonial mengenai komodifikasi pengetahuan tradisional, dengan menegaskan bahwa praktik perawatan tubuh tradisional bertahan melalui transformasi, bukan melalui kepunahan.